Analysis Risk Factor for Diarrhea in Toddlers of The Working Area at General Hospital Indonesia - Suarayasa, Ketut; Suriati, Ni Made; Anugrah, Ferry; Abkari, Farkhan Febri (Jurnal Perilaku Kesehatan Terpadu, 2024)
Background: Diarrhea is a medical condition characterized by a change in the consistency of the feces, resulting in softer, thinner, or watery stools. It typically occurs more than three times per day. This condition is caused by pathogenic microorganisms and is influenced by various risk factors, including environmental conditions, community behavior, healthcare services, diet, education, and socio-economic status. Objective: To identify the risk factors that impact the occurrence of diarrhea in young children at the Mamboro Community Health Center. Research Design: This study employs a descriptive analytical method with a cross-sectional approach. The study included 74 respondents, divided into two groups: those with diarrhea and those without. Data were collected from primary sources through questionnaires and secondary data from KIA book records. The data were analyzed using the Chi-Square statistical method. Results & Findings: The study found a significant association between a history of exclusive breastfeeding (P=0.002, P<0.005) and a history of allergies (P=0.000, P<0.005) with the occurrence of diarrhea in toddlers at the Mamboro Health Center. Conclusion: The history of exclusive breastfeeding significantly impacts the occurrence of diarrhea in toddlers. Additionally, there is a strong correlation between a history of allergies and the incidence of diarrhea at the Mamboro Health Center.